Metal‐Organic Frameworks‐Derived Nickel–Iron Oxyhydroxide with Highly Active Edge Sites for Electrochemical Oxygen Evolution. Issue 10 (7th July 2022) - Lan, Bi-Liu; Shao, Bing; Yang, Fu-Jie; Pang, Wei; Guo, Zeping; Meng, Ting; Zhang, Zhong; Huang, Jin
Abstract : Accurate introduction of catalytic active sites to precise locations on the catalyst surface is a challenge in designing and synthesizing high‐efficiency catalysts. Herein, the α phase nickel–iron oxyhydroxide ( α ‐NiFeO x H y ) rich of nickel active edge sites is electrochemically in situ generated from Fe‐square acid metal–organic framework precursor deposited on nickel‐containing electrode matrixes, which revealed superior oxygen evolution reaction performance signified by an overpotential of 167 mV to achieve a current density of 10 mA cm −2 in alkaline electrolytes. Notably, the as‐prepared metal oxyhydroxide exhibits long‐term electrochemical durability in 10 mA cm −2 for over 1080 h. By integrating the electrochemical evidence, Mössbauer spectroscopy, X‐Ray photoelectron spectroscopy, and density functional theory calculations, the nickel species enriched on the exposed edge facet of the as‐synthesized α ‐NiFeO x H y are proposed to be the highly catalytic active site. This study provides an expedient and energy‐efficient approach to in situ electrochemical fabrication of high‐performance NiFeO x H y oxygen evolution reaction catalysts from metal‐organic frameworks. Abstract : The ultra‐microporous Fe‐based metal‐organic frameworks are in situ electrochemically transformed into α ‐NiFeO x H y from the surface to the interior, and the ultra‐high active edge‐site nickel originating from the dissolution and release of the nickel substrate during the oxygen evolution reaction test.